Determinants of Santri’s Decision to Enroll in Islamic Boarding Schools: The Role of Life Skills, Personal Branding, and Gender Equality Perception through Trust and Value - Zainal Umam; Ali; Rifqy Roosdhani , Mohamad (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study employed a quantitative approach involving 180 students of Pondok Pesantren Hasyim Asy’ari Bangsri Jepara, selected using the Slovin formula from a total population of 280 students. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that life skills have a positive and significant effect on the decision to enroll, both directly and indirectly through perceived trust and perceived value. Personal branding does not have a direct effect on the enrollment decision; however, it significantly influences perceived trust and perceived value. Perceived gender equality is found to have the strongest direct and indirect effects on the decision to enroll, as well as a significant effect on perceived trust and perceived value. Furthermore, perceived trust and perceived value play significant mediating roles, confirming that the decision to enroll is the result of an evaluative process based on trust and long-term perceived benefits. These findings suggest that enrollment decisions are not solely determined by institutional image, but rather by educational substance, environmental fairness, and the trust and value perceived by students and their parents. Therefore, Islamic boarding schools should prioritize strengthening life skills, fostering inclusive environments, and building trust as key strategies to attract prospective students.